ANALISIS PERENCANAAN PENGGUNAAN PAGU ANGGARAN DALAM MENINGKATKAN EFEKTIVITAS KEGIATAN DI BIDANG PARIWISATA PADA DINAS KEPEMUDAAN OLAHRAGA DAN PARIWISATA KOTA SUKABUMI: ANALISIS PERENCANAAN PENGGUNAAN PAGU ANGGARAN DALAM MENINGKATKAN EFEKTIVITAS KEGIATAN DI BIDANG PARIWISATA PADA DINAS KEPEMUDAAN OLAHRAGA DAN PARIWISATA KOTA SUKABUMI - Kanias, Gia (Program Studi Sistem Informasi Akuntansi Kampus Kota Sukabumi, 2023)
ABSTRAK Gia Kanias (2030615001) Planning Analysis on the Use of Budget Ceilings in Increasing the Effectiveness of Activities in the Tourism Sector at the Sukabumi City Sports and Tourism Youth Service. The Sukabumi City Youth, Sports and Tourism Office is an institution that plays a role in assisting the Mayor in carrying out government affairs in the Youth, Sports and Tourism Sector which are the regional authority and Assistant Tasks assigned to the Region. This study aims: (1) To explain how budget planning is passed down to SKPD. (2) To explain how the budget ceiling is used in the tourism sector for one year. (3) To explain how the effectiveness of budget planning in the field of tourism. This research method is descriptive qualitative, namely by going directly to the field which was carried out at the Sukabumi City DISPORAPAR. Data obtained by conducting observations, interviews and Documentation Studies. The steps taken for research purposes (1) conduct research on how the budget ceiling can fall to each SKPD/Dinas. (2) Conduct research on how budget ceilings are used in the tourism sector. (3) calculating effectiveness by looking at the data in the 2020-2021 Tourism Sector budget realization report. The results of the research conducted concluded that: (1) The process of preparing the regional income and expenditure budget in the Disporapar of Sukabumi City, especially the Tourism Sector, is all in accordance with Permendagri Number 21 of 2011. (2) The budget ceiling used in the tourism sector has followed the correct flow that has been determined by the head of planning and finance disporapar. (3) The implementation of the budget at the Disporapar City of Sukabumi for the 2020-2021 Fiscal Year has been effective. It was found that the percentage ratio for 2020 is 98% which can be said to be effective and for 2021 is 100% which can be said to be very effective. In the government, especially in the tourism sector, it has carried out a maximum effectiveness of 100% because if more than 100% it is considered a waste of the budget and inefficient. Keywords: Use of Budget Ceilings in Increasing the Effectiveness of Activities in the Tourism Sector at the Sukabumi City Youth, Sports and Tourism Office